Resensitizing β‐Lactams by Reprogramming Purine Metabolism in Small Colony Variant for Osteomyelitis Treatment - Tingwang Shi; Qiong Wu; Zesong Ruan; Zhiyuan Luo; Wenbo Wang; Zhao Guo; Yihong Ma; Xin Wang; Guangyu Chu; Han Lin; Min Ge; Yunfeng Chen (Advanced Science)
Abstract Small colony variant (SCV) is strongly linked to antibiotic resistance and the persistence of osteomyelitis. However, the intrinsic phenotypic instability of SCV has hindered a thorough investigation of its pathogenic mechanisms. In this study, phenotypically stable SCV strains are successfully recovered from clinical specimens, characterized by elevated drug resistance and reduced immunogenicity. Multi‐omics analysis revealed that the acquired high drug resistance is associated with altered flux in the purine metabolism pathway, attributable to mutations in the hypoxanthine phosphoribosyltransferase (hpt) gene. Furthermore, this study innovatively discovered that lonidamine, an inhibitor of cellular energy metabolism, can effectively mitigate SCV resistance to β‐lactam antibiotics, thereby facilitating its eradication. The underlying mechanism involves the reprogramming of purine metabolism. Therefore, a co‐delivery system for lonidamine and oxacillin is constructed with amino‐modified dendritic mesoporous silica as a carrier, which showed high efficacy and safety in combating SCV both in vitro and in vivo experiments. Overall, this study elucidated the pathogenic mechanisms of a class of clinically isolated SCV isolates with hpt mutations and provided a paradigm for treating SCV‐associated osteomyelitis by reprogramming purine metabolism.